Alces americanus Clinton 1822 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alces americanus Clinton 1822 Alces americanus Clinton 1822, Letters on the natural history … of New York: 193. Type Locality: "Country north of Whitestown". USA, New York, probably in the western Adirondack region. Vernacular Names: Moose. Subspecies:: Subspecies Alces americanus subsp. americanus Clinton 1822 Subspecies Alces americanus subsp. cameloides Milne-Edwards 1867 Distribution: Russia (E Siberia), east of the Yenisei River east to Anadyr region (E Siberia) and south to N Mongolia and N China (N of Inner Mongolia and Manchuria). N America in Canada and N USA (including Alaska); introduced to New Zealand where now extinct. Conservation: IUCN – Lower Risk (nt) as A. alces cameloides . Discussion: Subspecies limits follow Geist (1998). Characters diagnosing species not fully confirmed for cameloides . Cervus americanus Clinton, 1822 is preoccupied by Cervus americanus Erxleben, 1777 (= Odocoileus virginianus ), a name used in the literature that has not been declared to be unavailable. It is probably a nomen oblitum and the familiar name Alces americanus (Clinton, 1822) continues to be used here. Cervus coronatus Lesson, 1827 (= C. coronatus É. Geoffroy Saint-Hilaire, 1803), based on a single rack, is usually cited as a synonym of Alces alces but is reputedly from America. It is much too small to be a Moose (C. H. Smith, 1827), and is possibly an aberrant Rangifer tarandus , according to Blyth (1860). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 653, DOI: 10.5281/zenodo.7316519